HOW AN ACADEMIC MANAGEMENT APPLICATION CAN REDUCE DROPOUTS IN HIGHER EDUCATION - Santos, Alexandre José Peixoto dos; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2024)
This study addresses the challenge of reconciling academic and personal life, which often results in high dropout rates in higher education. It is proposed to develop an academic management mobile application with the aim of improving student organization and reducing school dropout rates. The main objective is to describe the application development process, which offers features such as deadline monitoring, attendance control and personalized alerts to increase student retention. A literature review was carried out to identify the main requirements, followed by the creation of medium fidelity prototypes and modeling of the system with UML diagrams. The work was done in Java in the Android Studio environment. The results indicate that features such as personalized notifications, attendance control and activity scheduling can support the organization of classes and reduce the risk of dropout. Although the development of the application is still ongoing, it has great potential to improve academic management. The next steps include testing in real environments to validate its functionalities and interface.
Keywords: dropout; academic management; application; higher education; technology